Peran Masyarakat dalam Pengelolaan Sampah di Bank Sampah - Marwaji, Marwaji; Hasibuan, Bernard (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
Until now, the waste problem has not been resolved properly. The increase in the amount of waste along with the increasing population in an area has a huge impact, not only on the environment, but also on health, the economy and society. One effective step in managing waste is through a waste bank program initiated by the community to reduce the volume of waste produced. This research aims to provide an overview of the benefits of implementing the waste bank program, both for society and the environment. It is hoped that this research can reveal how the waste bank program can increase public awareness in sorting waste and reduce the amount of waste thrown into final landfills. Apart from that, this research also aims to explore the economic potential that can be generated from well-managed waste, such as increasing income for the communities involved in the program. By using a quantitative approach, it is hoped that this research can provide useful recommendations for improving implementation in the future.